Three Year Review Of The Marine Minerals Technology Center Ocean Basins Division - Michael J. Cruickshank (International Marine Minerals Society, 1991)
The University of Hawaii, Ocean Basins Division (OBD) shares, equally with the University of Mississippi, Continental Shelf Division (CSD), congressional funding for the Marine Minerals Technology Center, a Generic Minerals Center under the U.S. Department of the Interior's Mineral Institutes Program. The State of Hawaii supports the program by the provision of salaries for the Executive and Technical Directors and by the provision of fiscal, administrative, and facilities support through the Hawaii Natural Energy Institute, the Research Corporation of the University of Hawaii, and the School of Ocean and Earth Science and Technology. The Center's program of research, technology development and education is multi-disciplinary and international in scope. Activities since the MMTC/OBD was established in June 1988 have included: Research projects * Development of a Free-Fall Seafloor Hard Substrate Corer. * The Microtopography of Manganese Crust deposits. * Evaluation of the Cobalt Crust Continuum on Seamounts in the Hawaiian Exclusive Economic Zone. * Graphite Furnace Atomic Absorption Spectrometer. * Computer Aided Design Methodology for Power, Communication and Strength Umbilicals. * Characterization and Environmental Impact Assessment of Tropical * Reef-derived sands for Beach Replenishment.